Timing of initiation of oral anticoagulants in patients with acute ischemic stroke and atrial fibrillation comparing posterior and anterior circulation strokes. (December 2020) - Paciaroni, Maurizio; Agnelli, Giancarlo; Giustozzi, Michela; Tsivgoulis, Georgios; Yaghi, Shadi; Grory, Brian Mac; Furie, Karen L; Tadi, Prasanna; Zedde, Marialuisa; Abdul-Rahim, Azmil H; Dawson, Jesse; Lees, Kennedy R; et al.
Introduction: The aim of this study in patients with acute posterior ischaemic stroke (PS) and atrial fibrillation (AF) was to evaluate (1) the risks of recurrent ischaemic event and severe bleeding and (2) these risks in relation with oral anticoagulant therapy (OAT) and its timing. Materials and Methods: Patients with PS were prospectively included; the outcome events of these patients were compared with those of patients with anterior stroke (AS) which were taken from previous registries. The primary outcome was the composite of stroke recurrence, transient ischaemic attack, symptomatic systemic embolism, symptomatic cerebral bleeding and major extracranial bleeding occurring within 90 days from acute stroke. Results: A total of 2470 patients were available for the analysis: 473 (19.1%) with PS and 1997 (80.9%) with AS. Over 90 days, 213 (8.6%) primary outcome events were recorded: 175 (8.7%) in patients with AS and 38 (8.0%) in those with PS. In patients who initiated OAT within 2 days, the primary outcome occurred in 5 out of 95 patients (5.3%) with PS compared to 21 out of 373 patients (4.3%) with AS (OR 1.07; 95% CI 0.39–2.94). In patients who initiated OAT between days 3 and 7, the primary outcome occurred in 3 out of 103 patients (2.9%) with PS compared to 26 out of 490 patients (5.3%) with AS (OR 0.54; 95% CI 0.16–1.80). Discussion: our findings suggest that, when deciding the time to initiate oral anticoagulation, the location of stroke, either anterior or posterior, does not predict the risk of outcome events. Conclusions: Patients with PS or AS and AF appear to have similar risks of ischaemic or haemorrhagic events at 90 days with no difference concerning the timing of initiation of OAT.